2015
DOI: 10.1890/15-0518.1
|View full text |Cite
|
Sign up to set email alerts
|

Parasite species richness and intensity of interspecific interactions increase with latitude in two wide‐ranging hosts

Abstract: Abstract. Although the latitudinal diversity gradient is a well-known and general pattern, the mechanisms structuring it remain elusive. Two key issues limit differentiating these. First, habitat type usually varies with latitude, precluding a standardized evaluation of species richness. Second, broad-scale and local factors hypothesized to shape diversity patterns covary with one another, making it difficult to tease apart independent effects. Examining communities of parasites in widely distributed hosts can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 57 publications
(79 reference statements)
2
37
0
Order By: Relevance
“…Merino et al (2008) failed to find a significant relationship between latitude and richness of three genera of haematozoa (blood parasites) in 26 species of forest birds in Chile. Thieltges et al (2009) and Torchin et al (2015) each sampled two snail host species for parasitic trematodes. Schemske et al (2009) and Poulin (2014) suggested that investigations of the LDG of parasites within a single, widely-distributed host species may provide stronger tests of latitudinal patterns than studies combining host taxa, given that the taxonomic composition of host and parasite communities change between temperate and tropical areas and might therefore be incomparable (Poulin 2014).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 99%
See 2 more Smart Citations
“…Merino et al (2008) failed to find a significant relationship between latitude and richness of three genera of haematozoa (blood parasites) in 26 species of forest birds in Chile. Thieltges et al (2009) and Torchin et al (2015) each sampled two snail host species for parasitic trematodes. Schemske et al (2009) and Poulin (2014) suggested that investigations of the LDG of parasites within a single, widely-distributed host species may provide stronger tests of latitudinal patterns than studies combining host taxa, given that the taxonomic composition of host and parasite communities change between temperate and tropical areas and might therefore be incomparable (Poulin 2014).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 99%
“…Using small mammals from Brazil, Linardi and Krasnov (2013) found that flea species richness was not significantly related to latitude and mite species richness was significantly and positively correlated with latitude, with mite richness increasing with distance from the equator. Torchin et al (2015) examined trematodes along the east and west coasts of the southern United States to Panama and found that species richness increased with increasing latitude. However, few studies have explored the LDG within a host species, and even fewer have used a globally-distributed species, as recommended by Poulin (2014).…”
Section: A Review Of Past Studies On the Latitudinal Diversity Pattermentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic snails offer an excellent system in which to investigate patterns of symbiont richness and their underlying drivers (e.g., Torchin et al 2015). They are the obligate first intermediate hosts for parasitic flatworms (trematodes), some of which affect the health of humans, domestic animals, or wildlife (Crompton 1999; Johnson et al 1999; King et al 2005; Gryseels et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Morand and Krasnov, 2008;Dunn et al, 2010;Kamiya et al, 2014;Poulin, 2014;Smith et al, 2014;Torchin et al, 2015 The interface between parasitology, community ecology, and ecosystem science How do parasites and pathogens affect communityand ecosystem-scale processes, including nutrient cycling, disturbance regimes, primary production, and community composition? Can this information be used to enhance our understanding of global parasite biodiversity and the identification of disease hotspots?…”
mentioning
confidence: 99%